The complex relationship between international tourism demand and economic growth: An analysis on Central and Eastern European economies - Alina Bădulescu; Daniel Bădulescu; Ramona Simuț (Amfiteatru Economic Journal, 2018)
Tourism is widely considered as driver for economic growth, and the "tourism-led-growth hypothesis" is often investigated in the literature. However, there is very limited literature examining how economic growth impacts tourism, an impact which is usually tacitly accepted, without being analytically investigated. In this paper we examine the impact of the economic growth on the number of international tourism arrivals and also on the international tourism receipts during 1995-2015, in Central and Eastern European economies, by using the Autoregressive Distributed Lag (ARDL) model. The bounds F-statistics for cointegration test provide evidence of a long-term relationship between the international tourism number of arrivals and GDP per capita only for Bulgaria, Croatia, Czech Republic, Estonia, Lithuania, Slovenia, Romania and Slovakia. Between international tourism receipts and GDP per capita we find a long-term relationship only for Bulgaria, Croatia, Slovakia, Latvia, Estonia, Poland, Romania and Czech Republic. We also explore causal relationship between the variables by using an error-correction- based Granger causality model (short-run and long-run), finding different unidirectional / bidirectional short/long-term relationships between international tourism demand (measured by two proxies: international tourist arrivals and international tourism receipts) and economic growth (measured by GDP per capita), in different countries. The paper contributes to better understanding the nature and the direction of the relationship between tourism sector and economic growth, aiming not only to enrich the literature in the field, but also to design specific economic growth policies with an impact on tourism sector
Keywords: Z32; L83; C32; O11; O52; 330; international tourism demand; economic growth; Granger causality; ARDLmodel; Central and Eastern European countries